MENGATASI FENOMENA GALAU DENGAN KONSEP TAZKIYATUN NAFS MENURUT TAFSIR AL MISBAH KARYA QURAISH SHIHAB - Renilda Vili Andini; Luthviyah Romziana (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Anxiety is a psychological phenomenon frequently experienced by individuals, particularly among adolescents and young adults, due to social, academic, and emotional pressures. Although the Qur’an does not explicitly mention the term “anxiety,” this emotion is often associated with huzn (sadness), raiba (doubt), and ya’s (despair). Quraish Shihab’s Tafsir Al-Mishbah offers a deeper understanding of this phenomenon and its solution through the concept of Tazkiyatun Nafs (purification of the soul). This study aims to analyze the concept of anxiety according to Quraish Shihab in Tafsir Al-Mishbah and explore how Tazkiyatun Nafs serves as a solution. A qualitative research method is applied using a library research approach, focusing on thematic exegesis (tafsir maudhui). The primary source of this study is Tafsir Al-Mishbah, examined through content analysis to understand the concept of anxiety and the relevance of Tazkiyatun Nafs in the Qur’an. Quraish Shihab explains that anxiety is an emotional condition that can be alleviated through spiritual approaches. The concept of Tazkiyatun Nafs in Tafsir Al-Mishbah emphasizes soul purification through key practices: (1) engaging in dhikr to attain inner peace (QS. Ar-Ra’d: 28), (2) practicing patience and gratitude in facing trials (QS. Al-Baqarah: 286), (3) maintaining sincerity in worship and deeds (QS. Al-Bayyinah: 5), and (4) performing sincere repentance (taubat nasuha) to achieve spiritual tranquility (QS. At-Tahrim: 8). This study concludes that anxiety can be categorized as both a psychological and spiritual issue that can be addressed through Tazkiyatun Nafs, as elaborated in Tafsir Al-Mishbah. By adopting these principles, individuals can enhance emotional resilience and attain inner peace through the guidance of the Qur’an.